The journey of discovery in co-creating knowledge to find a new way of working in municipal home care-seven lessons learned in a participatory appreciative action and reflection study - Inger James; Annica Kihlgren; Sofia Tavemark (Health Psychology and Behavioral Medicine)
Purpose The study is part of a larger structural change programme, where Participatory Appreciative Action and Reflection (PAAR) has been used with the aim of changing home care practices to align with individuals’ needs and goals. The purpose of this study was to describe how the knowledge process in PAAR was conducted to develop a new way of working based on the individual’s needs and goals in home care.Method A total of 160 co-researchers i.e. older persons, relatives, staff, administrators, first-line managers, case managers and persons from the authority were included in the study. Data was collected through fieldwork, including interviews, participant observations, informal conversations, focus group discussions, reference groups, and appreciative inquiry circles.Results Co-creating knowledge was revealed as a three-step process: preparation for access to the field, being together in the field, and leaving the field. Each step describes several cycles of how the PAAR process proceeded, with actions leading to reflections and vice versa, which drove the knowledge process forward.Conclusions The knowledge process of PAAR, gave rise to seven lessons learnt for future practice development: Contact pathways and trusting relationships, Loving struggle over time, An appreciative gaze, Patience and courage, Different ways of learning, A shared goal and Flexibility to adapt PAAR to changes in the field.